2023
DOI: 10.3389/fgene.2023.1100170
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of prognosis of cuproptosis-related oxidative stress genes in multiple myeloma

Abstract: Introduction: Multiple myeloma (MM) is a highly heterogeneous hematologic malignancy. The patients’ survival outcomes vary widely. Establishing a more accurate prognostic model is necessary to improve prognostic precision and guide clinical therapy.Methods: We developed an eight-gene model to assess the prognostic outcome of MM patients. Univariate Cox analysis, Least absolute shrinkage and selection operator (LASSO) regression, and multivariate Cox regression analyses were used to identify the significant gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
(71 reference statements)
0
4
0
Order By: Relevance
“… 23 The results of recent studies have emphasized the potential utility of CRGs in the development of prognostic models for MM. 24 , 25 These findings indicate the existence of an association between CRGs and MM. However, the primary focus of these studies has been placed on the use of CRGs for the prediction of MM prognosis rather than on its diagnosis.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“… 23 The results of recent studies have emphasized the potential utility of CRGs in the development of prognostic models for MM. 24 , 25 These findings indicate the existence of an association between CRGs and MM. However, the primary focus of these studies has been placed on the use of CRGs for the prediction of MM prognosis rather than on its diagnosis.…”
Section: Introductionmentioning
confidence: 72%
“…It is worth noting that previous studies have reported the utilization of CRGs for prognostic prediction in MM 24,25 . However, given the significance of early diagnosis and effective management for improving patients' quality of life and reducing the burden of symptoms and complications, an exploration of the potential impact of CRGs on predicting the diagnosis of MM is imperative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations